(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The use of the Kida model and understanding its impact in evaluating the ability of the bank, the research sample, to anticipate the future in accordance with the International Assurance Engagement Standard 3400. The research aims to determine the validity of the assumptions made by the bank’s management, which relied on some financial indicators and ratios extracted from the statements for the period from (2018-2022), which helps The bank’s management evaluates the activity and takes appropriate decisions to correct its financial position and anticipate any difficulties it faces to take sound measures to correct them.The most prominent findings reached in this research are that (Sh Bank) does not have a strong financial position and therefore cannot be in a good position towards customers during the years of study and is exposed to successive financial difficulties and thus is unable to anticipate the future in accordance with the international assurance engagement standard 3400.The most prominent recommendations reached by the research are the necessity of hiring teams of professional financial analysts for the purpose of training and developing bank employees to benefit from their experience in how to address problems that could affect the bank’s activity, and how to mitigate the severity of these problems if they are inevitable and cannot be overcome.